Tin Oxide Quantum Dots and Poly(Ortho-Chloroaniline)-Supported SnO2 Nanocomposite for Dye-Wastewater Photocatalysis, Reuse, and Seed-Germination Assessment - Walied A. A. Mohamed; Hala T. Handal; Mahmoud A. M. Ahmed; Nahla M. Badawy; Mona M. Fawzy; Ibrahem A. Ibrahem; Hanan A. Mousa; Hoda R. Galal; M. S. A. Abdel-Mottaleb; Ammar A. Labib (Water, Air, & Soil Pollution, 2026)

In-silico Exploration of Marine Algae-derived Compounds as the Potential Inhibitors of Polycomb Group Ring Finger 4 Protein - Md Al Saber; Sowmitro Das; S. M. Istiaque Hamim; Sadia Jannat Tauhida; Kazi Sneha Chhando; Partha Biswas; Mohaimenul Islam Tareq; Faria Khondokar Noumi; Shaharia Akter Borsha; Labib Sahariar Siam; Roney Miah; Md. Nazmul Hasan (Journal of Pharmaceutical Innovation, 2026)

Exploring the effect of bronopol exposure length on the suppression of Aeromonas hydrophila infection in nile tilapia (Oreochromis niloticus L.) - Zizy I. Elbialy; Eman M. Moustafa; Amira A. Omar; Abdallah S. Salah; Ahmed Elsheshtawy; Mohammed M. Zayed; Marwa F. Abdel-Kader; Hani Y. Labib; Hossam I. Kadira; Dina B. Barsem; Ahmed E. Elshafey; Sayed M. Aboleila; et al. (Veterinary Research Communications, 2026)

Male reproductive toxicity induced by chronic dinotefuran exposure: In vivo and in silico evidence and the ameliorative role of Rosmarinus officinalis - Samah S. Arafa; Ibrahim.M. Ammar; Ragaa A. Eisa; Mariam E. Labib; Ahmed M. Atwa; Marwa O. Gabr (Reproductive Toxicology, 2026)

Assessment of zootechnical parameters, intestinal digestive enzymes, haemato-immune responses, and hepatic antioxidant status of Pangasianodon hypophthalmus fingerlings reared under different stocking densities - Mohamed A. A. Zaki; Hala Saber Khalil; Belal W. Allam; Riad H. Khalil; Mohammed F. El Basuini; Abd El-Aziz M. Nour; Eman M. H. Labib; Islam S. E. Elkholy; Marc Verdegem; Hany M. R. Abdel-Latif (Aquaculture International, 2023)
A 3-month experiment was designed to investigate the effects of different stocking densities on growth, stress markers, intestinal digestive enzymes, hepatic antioxidant biomarkers, serum immunity, and survivability of striped catfish, Pangasianodon hypophthalmus . The relationship between fish stocking densities and water quality parameters was also assessed. Healthy fish ( n = 1260 individuals, 17.52 ± 0.20 g) were raised in twelve fiberglass tanks. Triplicate fish groups with stocking densities of 60, 90, 120, or 150 fish per 1 m 3 were designed, further referred to as SD60, SD90, SD120, and SD150 groups. Fish feeding was done using a commercially purchased well-balanced diet three times per day with a feeding rate of 3% of the wet fish weight. Results revealed that un-ionized ammonia, nitrite, and pH were significantly elevated, and dissolved oxygen levels were decreased significantly with increasing the stocking densities. The survival rates and growth significantly decreased with increasing fish stocking densities. The intestinal lipase, protease, trypsin, and amylase enzymes decreased significantly ( P 3 . Conversely, serum stress biomarkers (such as blood glucose and cortisol), transaminases, alkaline phosphatase, and blood urea nitrogen were significantly elevated with increasing stocking densities. Hepatic CAT, SOD, and T-AOC were decreased; meanwhile, hepatic MDA levels were significantly increased, together with the stocking rates. In the end, we found that the SD150 group recorded the lowest growth rates, immune responses, and antioxidant capacity and the highest stress markers as blood glucose and cortisol. In this context, we can conclude that the stocking 60 fish/m 3 resulted in better growth, survival, immunity, antioxidant status, and overall performances of striped catfish. Graphical Abstract

Controlled Drainage and Irrigation Regime for Improving Some Soil Properties and Wheat Production, Sahl El-Tina, Sinai Peninsula, Egypt - A. S. El-Hassanin; M. R. Samak; Y. Atta; Somma M. H. Labib (Water Conservation Science and Engineering, 2022)

Eco-Friendly Tadalafil Surfactant-Free Dry Emulsion Tablets (SFDETs) Stabilized by In Situ Self-Assembled Aggregates of Natural Oil and Native Cyclodextrins - Shaimaa M. Badr-Eldin; Gihan S. Labib; Mona H. Aburahma (AAPS PharmSciTech, 2019)

Comparative transcriptomic analyses to scrutinize the assumption that genotoxic PAHs exert effects via a common mode of action - S. Labib; A. Williams; C. H. Guo; K. Leingartner; V. M. Arlt; H. H. Schmeiser; C. L. Yauk; P. A. White; S. Halappanavar (Archives of Toxicology, 2016)